Women and Children of the Mills: An Annotated Guide to Nineteenth-Century American Textile Factory Literature (review) - Robinson, Lillian S (Resources for American Literary Study, 2001)
Resources for American Literary Study 27.2 (2001) 291-294 , The Industrial Revolution is arguably the best-documented and least-understood phenomenon in American social history. An unusually high literacy level among the young New England women who constitute a major part of the first generation of textile workers accounted for a plethora of their own imaginative and autobiographical writings, as well as for an enormous body of popular literature directed to the eager audience of factory girls. This material gives the present-day reader access to the experience and mentality of the mill workers, and, with corporate and technological history, draws a multi-faceted and complex picture of the process of industrialization of nineteenth-century America., It would be more accurate, however, to say that this rich store of material is a potential source of such enlightenment, since it remains largely unexplored by literary [End Page 291] scholars and critics. Whether as cause or result of this obscurity, nineteenth-century American literature produced no fictional equivalent of George Eliot's Middlemarch (1872), with its panoramic investigation of changing material and human relations in England's transition to industrial capitalism, nor did it boast even a more modest proletarian novel on the scale of Richard Tressell's Ragged-Trousered Philanthropists (1914), with its personalization and explication of the new economic forces at work in society. And twentieth-century American historiography has yielded no work of scholarship remotely comparable to E. P. Thompson's monumental Making of the English Working Class (1963). Conversely, the dominant narrative of nineteenth-century America, literary or historical, is assumed to lie elsewhere, in the cultural flowering of New England, the Westward expansion, and the Civil War., The time is long past for an American Middlemarch, but it is never too late to analyze and reinterpret the making of the U. S. working class, a project that would add another important dimension to our understanding of nineteenth-century America. The documentation is there and, in Women and Children of the Mills, Judith Ranta provides what amounts to an exhaustive documentation of that documentation. Indeed, in the face of Ranta's painstakingly thorough listing and cross-listing, it feels almost churlish to question the need for such a volume. But question it I do. Women and Children of the Mills is a contribution to Greenwood's series, Bibliographies and Indexes in American Literature. Similar questions might be raised about the ultimate necessity and value of a number of other items in that series. Did the world really cry out for a book-length bibliography on John Updike or Laura Ingalls Wilder? Was it languishing in its ignorance, before Greenwood stepped into the breach, for a full volume devoted to proverbs in the works of Eugene O'Neill? But, however heavy-handed the series' treatment of some rather lightweight material, its format serves the present topic quite well. Even features that may strike the reviewer as tedious repetitions of biographical and bibliographical information will probably be a godsend to the actual user--which is to say, practically anyone else who has occasion to pick up the volume--homing in on a particular author, periodical, locality, or theme., Ranta organizes the main body of her material into fourteen categories. Most of these are thematic, ranging from "Women Leaving Home: Work, Independence, Women's Rights" through "Scenes of Factory Life" and "Working Children" to separate chapters on pro- and anti-strike literature and "Charity and Reforms." One category, "Offerings and Voices: Periodicals of Women's Work," focuses on the sites of publication, providing full descriptions of the various magazines that published fiction by and about mill girls. Another unusual taxonomy, by literary genre, is the chapter on "escape" reading, romances and...
Keywords: Business History and gender